An Overreview of the Sociocultural Theory and Vocabulary Development: Tinjauan Singkat Teori Sosial Budaya dan Pengembangan Kosakata - Alkurtehe, Khaled Ali Mohammed; Dzakiria, Hisham (Universitas Muhammadiyah Sidoarjo, 2018)
Vegotesky theory is a paramount for the vocabulary development with its multidimensional approach, which has the impact on the cognitive affective contextual aspects and social interaction.Socio-cultural theory(SCT) is the mental development of specific sphere human. It also concerns mediation and the different kinds of mediation tools adopted and valued by society.This paper highlighted that learning as a mediated process in social in origin and then becomes individual as a result of linguistically mediated interaction between the child and more experienced members of the society including parents, teachers, and peers. The relation of mediation of SCT and environment is to enhance vocabulary development in teaching EFL students. It also helps EFL students to use the target language in their daily life .With the help of this theory, the students can master vocabulary and improve their language.This theory focuses on the interaction with the students and shows the social environment. It links the learners with the trainer, if a child/student gets a guidance in an appropriate way he/she can learn more and can enhance his/her capacity of learning.This study tried to look at the influence of SCT on learning and teaching vocabulary. Consequently, This study recommends the use of the SCT while teaching EFL Libyan learners to enhance English language vocabulary.